100 wonders of India - Roli books (pub.) (New Delhi Roli books, 2019)
Travellers in ancient times marvelled at seven man-made wonders located in various countries bordering on the Mediterranean. Over hundreds of years since then, civilisations have risen and declined, the world has been built and rebuilt, and many more works of human genius lie scattered across geographies and eras. Exploration and discovery has revealed more of nature's wonders too, that stretch and humble human imagination. India, with an area of well over three million square kilometres, is a continent within a continent. Within the folds of an astounding 5,000-year-old history and vast multitude of landscapes that include the world's highest mountains, great rivers, long coastlines, deserts and dense forests, is an awesome legacy of man-made and natural wonders - some legendary for long, others no less magnificent but not so well known. Each is described with details of history and brought to life with vivid colour images. Also included is useful information for travellers, all of which blend to make this an attractive book for history buffs, art lovers, nature enthusiasts and all those who want to be acquainted with India's magnificent wonders.
Keywords: Indian history